LEGAL SERVICES UNIT FOR CHILDREN UNDER CHILD-FRIENDLY SERVICES: A PERSPECTIVE ON CHILD PROTECTION THROUGH LEGAL AID - Hussain, Mujataba Noorul; Mali, Mahaveer Prasad; Rehman, Sadaqat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Children face complex and layered vulnerabilities—ranging from psychological trauma to systemic exclusion from justice mechanisms. This paper explores how a dedicated Legal Services Unit for Children under the Child-Friendly Services framework can serve as a comprehensive protective tool. The analysis extends to the need for an intra-agency child protection mechanism, inclusion of mental health rights, and the development of an institutionalized structure that ensures holistic support, access to justice, and child empowerment.